Preparation method of SnO2 modified Co-B-C high-performance catalyst

CN119281345APending Publication Date: 2025-01-10XIAN TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411352059.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

[0004]通常情况下,在制备CoB催化剂过程中,CoB颗粒极易出现团聚,使有效表面积降低、活性位数目减少,从而导致催化NaBH4水解制氢的速率较小

Benefits of technology

[0024] 1. The catalyst prepared by the present invention has excellent catalytic performance, at 30°C, 5wt.% NaBH 4 In the reaction medium composed of 5wt.% NaOH and 5wt.% NaOH, the hydrogen production rate is as high as 13.20L·min -1 ·g Co -1 , activation energy as low as 30.4kJ·mol -1 .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281345A_ABST
    Figure CN119281345A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a SnO2 modified Co-B-C high-performance catalyst, which comprises the following steps: taking dry coffee grounds as a carbon source of a biomass carbon material, taking ZnCl2 as an activating agent, and obtaining biomass carbon by adopting a carbonization method; the catalyst with excellent catalytic hydrogen production performance is further synthesized by means of co-impregnation and in-situ reduction; the problem that a Co-B catalyst is prone to agglomeration in the reaction process is solved through cooperation of doped biomass carbon and SnO2, and the prepared catalyst is uniform in particle distribution and shows high activity, low activation energy, good cycling stability and strong ferromagnetism for catalyzing the NaBH4 hydrolysis hydrogen production reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalytic hydrogen production and relates to a SnO 2 Preparation method of modified Co-B@C high-performance catalyst. Background Art

[0002] At present, the fossil energy crisis is gradually intensifying and environmental pollution problems are becoming increasingly prominent, so it is urgent to find an alternative new energy source. Hydrogen energy, as a clean and efficient secondary energy source, has attracted great attention worldwide, and the efficient use of hydrogen energy has become a hot topic in current research. Although hydrogen has shown obvious advantages as a fuel, it is still a severe challenge to find a safe, convenient and practical hydrogen storage technology.

[0003] Chemical hydrides, especially NaBH 4 , has a high hydrogen storage capacity, with a hydrogen content of up to 10.8wt.%. The hydrogen produced during the hydrolysis process is extremely pure and does not emit harmful gases. At the same time, it does not require external energy and has a high energy utilization rate. 4 Hydrogen production by hydrolysis is safe, green and convenient, so it is considered to be an ideal new chemical hydrogen storage material and has attracted special attention from researchers. 4 It is necessary to use a suitable catalyst to promote the hydrolysis reaction in order to achieve efficient and rapid hydrogen production. Precious metal catalysts such as Pt, Pd, Ru, etc. show excellent activity, but their high prices limit their wide application. At present, non-precious metal catalysts represented by CoB are widely studied due to their high activity, low price and good stability.

[0004] Generally, during the preparation of CoB catalysts, CoB particles are prone to agglomeration, which reduces the effective surface area and the number of active sites, thus leading to the catalytic NaBH 4 The rate of hydrogen production by hydrolysis is low. However, in the process of catalyst synthesis, by controlling the specific conditions of the synthesis and adding appropriate additives, the dispersion of CoB particles can be significantly improved, and the performance of the catalyst can be significantly improved.

[0005] Based on this, the present invention aims to develop and prepare a catalyst with high activity and low activation energy that can improve the agglomeration phenomenon of CoB particles. Summary of the invention

[0006] In view of the above technical problems, the present invention aims to provide a SnO 2 The preparation method of the modified Co-B@C high-performance catalyst is to use dry coffee grounds as the carbon source of biomass carbon material, ZnCl 2As an activator, biomass carbon is obtained by carbonization method; further, a catalyst with excellent catalytic hydrogen production performance is synthesized by co-impregnation and in-situ reduction; the present invention is to dope biomass carbon and SnO 2 The two work together to overcome the problem of easy agglomeration of Co-B catalysts during the preparation process. The prepared catalyst particles are evenly distributed and have a good catalytic effect on NaBH 4 The hydrolysis reaction for hydrogen production exhibits high activity, low activation energy, good cyclic stability, and strong ferromagnetism.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A SnO 2 The preparation method of the modified Co-B@C high-performance catalyst is carried out in the following steps in sequence:

[0009] (1) Add dry coffee grounds to ZnCl 2 The solution was stirred evenly, and after impregnation for 12 hours, it was poured into a crucible and kept in a muffle furnace at 300°C for 30 minutes. After cooling to room temperature, it was taken out and ground, and then washed with deionized water until neutral, and dried at 100-120°C for 10-12 hours to obtain biomass carbon;

[0010] (2) Add the biomass carbon obtained in step (1) to CoCl 2 6H 2 O and SnCl 4 ·5H 2 O in a mixed solution, and ultrasonically mix until the mixture is uniform to obtain a solution;

[0011] (3) The solution obtained in step (2) was placed in a water bath at 25°C and NaBH 4 The alkaline solution is added to the solution obtained in step (2), and after the reaction is complete, the solution is centrifuged and washed with deionized water and ethanol three times respectively, and then placed in a vacuum drying oven to dry to obtain a catalyst.

[0012] As a limitation of the preparation method of the present invention, in step (1), the particle size of the dried coffee grounds is 100-150 mesh.

[0013] As another limitation of the preparation method of the present invention, in step (1), the dried coffee grounds and ZnCl 2 The mass ratio of the solution is 1:2.8.

[0014] As a third limitation of the preparation method of the present invention, in step (1), the ZnCl 2 The solution concentration is 3 mol / L.

[0015] As a fourth limitation of the preparation method of the present invention, in step (2), the CoCl 2 6H 2 O and SnCl 4 ·5H 2 The molar ratio of O is 68:1.

[0016] In the present invention, CoCl 2 6H 2 O and SnCl 4 ·5H 2 The molar ratio of Sn to Co-B@C is crucial and affects the catalytic performance of the catalyst. The addition of an appropriate amount of Sn additive to Co-B@C can increase the specific surface area of ​​the catalyst, promote the dispersion of Co-B particles, and increase the content of active Co, thereby significantly improving the catalyst's catalytic performance for NaBH 4 The presence of the auxiliary agent Sn also produces a synergistic effect with the active Co, which can make the active Co site more active for H + The adsorption strength of H + Transfer to Sn x+ Then it rapidly desorbs to generate H 2 , completing the catalytic cycle.

[0017] As a fifth limitation of the preparation method of the present invention, in step (2), the biomass carbon and CoCl 2 6H 2 The mass ratio of O is 1:32.4.

[0018] As we all know, the dispersion of the active components of the catalyst has a great influence on the performance of the catalyst. In the present invention, biomass carbon and CoCl 2 6H 2 O mass ratio will affect the dispersion of Co-B catalyst particles. When no biomass carbon is added or the addition amount is too low, the Co-B catalyst particles agglomerate seriously and the number of active sites is small, resulting in low catalyst activity. 2 6H 2 When the mass ratio of biomass carbon to CoCl was 1:32.4, the agglomeration of Co-B particles was significantly improved, the dispersion was significantly improved, the content of active Co increased and the electron density increased, which showed that the addition of appropriate amount of biomass carbon could significantly improve the catalytic activity of Co-B particles. 2 6H 2 When the mass ratio of O is greater than 1:32.4, the activity of the catalyst is significantly reduced because the catalytic active sites are covered by excessive biomass carbon.

[0019] As a sixth limitation of the preparation method of the present invention, in step (3), the NaBH 4The drop rate was 2 mL / min.

[0020] As a seventh limitation of the preparation method of the present invention, in step (3), the NaBH 4 The alkaline solution was prepared by dissolving 1.5 g of NaOH in 27 g of deionized water to obtain an alkaline solution, and then adding 1.5 g of NaBH 4 , stir and dissolve to obtain NaBH 4 of alkaline solution.

[0021] As the eighth limitation of the preparation method of the present invention, in step (3), the drying temperature is 60-70° C. and the time is 10-12 h.

[0022] The above technical solution of the present invention is taken as a whole, and each step is closely related and influences each other, which jointly determine the morphological characteristics and performance of the product.

[0023] The above technical solution has the following advantages or beneficial effects:

[0024] 1. The catalyst prepared by the present invention has excellent catalytic performance. At 30°C, 5wt.% NaBH 4 In the reaction medium composed of 5wt.% NaOH, the hydrogen production rate is as high as 13.20L·min -1 ·g Co -1 , the activation energy is as low as 30.4 kJ·mol -1 .

[0025] 2. The catalyst prepared by the present invention shows good cycle stability. 4 In the hydrolysis hydrogen production reaction, after 5 cycles of experiments, the catalyst still maintained 83.9% of its initial activity.

[0026] 3. The catalyst prepared by the present invention exhibits strong ferromagnetism, which enables the catalyst to be quickly separated and recovered from the solution. Compared with traditional non-magnetic catalysts, the recovery process is simpler and more thorough.

[0027] 4. The preparation process of the present invention is simple and easy to control, the reaction time is short, and it is easy to industrialize production and promote.

[0028] The present invention is suitable for preparing SnO 2 Modified Co-B@C high-performance catalyst.

[0029] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and specific implementation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1The XRD pattern of the catalyst prepared in Example 1 of the present invention;

[0031] Figure 2 This is a SEM image of the catalyst prepared in Example 1 of the present invention;

[0032] Figure 3 N of the catalyst prepared in Example 1 of the present invention 2 Adsorption / desorption isotherms and BJH pore size distribution diagram;

[0033] Figure 4 This is a graph of the hydrogen production rate of the catalyst prepared in Example 1 of the present invention;

[0034] Figure 5 Co 2p (a) and B1s (b) XPS spectra of the catalyst prepared in Example 1 of the present invention;

[0035] Figure 6 Hydrolysis hydrogen production diagram, lnk and 1 / T corresponding Arrhenius diagram of the catalyst prepared in Example 1 of the present invention;

[0036] Figure 7 This is a stability test chart of the catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.

[0038] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0039] Example 1

[0040] This example prepares a SnO 2 The preparation method of the modified Co-B@C high-performance catalyst, the preparation process and steps are as follows:

[0041] (1) Add 2 g of 100-150 mesh dried coffee grounds (RUMBA Italian coffee beans, the same below) to 4 mL of 3 mol / L ZnCl 2The solution was stirred evenly, and after impregnation for 12 hours, it was poured into a crucible and kept in a muffle furnace at 300°C for 30 minutes. After cooling to room temperature, it was taken out and ground into 100-150 meshes, and then washed with deionized water until neutral, and dried at 110°C for 12 hours to obtain biomass carbon;

[0042] (2) Add 0.05 g of the biomass carbon obtained in step (1) to 0.0068 mol CoCl 2 6H 2 O and 0.0001 mol SnCl 4 ·5H 2 O mixed solution, and ultrasonically mixed at 30°C for 1 h to obtain a solution;

[0043] (3) The solution obtained in step (2) was placed in a water bath at 25°C and 30 mL of NaBH 4 Alkaline solution (NaBH 4 The alkaline solution was prepared by dissolving 1.5 g NaOH in 27 g deionized water to obtain an alkaline solution, and then adding 1.5 g NaBH 4 , stir and dissolve to obtain NaBH 4 The alkaline solution) was added to the solution obtained in step (2) at a drop rate of 2 mL / min. After the reaction was complete, the mixture was centrifuged and washed with deionized water and ethanol for three times respectively, and then placed in a vacuum drying oven and dried in vacuum at 60° C. for 12 h to obtain a catalyst.

[0044] The prepared biomass carbon was subjected to organic element analysis, and the results are shown in the table below.

[0045]

[0046] It can be seen from the above table that the carbon content is 59.479wt.%, and its purity is much lower than commercial graphene and other carbon materials.

[0047] Figure 1 The XRD pattern of the catalyst prepared in Example 1 of the present invention is shown in the figure. It can be seen from the figure that a weak and broad diffraction peak is observed at 2θ=40°-50°, which corresponds to the amorphous structure of Co-B. The catalyst prepared in Example 1 of the present invention is tested by SEM and BET (such as Figure 2 and Figure 3 The catalyst is a nanosheet layered structure, the CoB particles are evenly distributed, and the specific surface area is 25.7 m 2 / g.

[0048] The catalyst prepared in Example 1 of the present invention was catalyzed by NaBH 4 The specific experimental steps of the hydrolysis hydrogen production experiment are as follows:

[0049] First, 10 mL of the mixed solution (composed of 5 wt.% NaBH 4 and 5wt.% NaOH) was added into a 100mL round-bottom flask, and the flask was placed in a water bath to ensure that the reaction temperature remained constant; then, 100mg of the catalyst prepared in Example 1 of the present invention was weighed and added into the mixed solution, and catalytic hydrolysis and hydrogen production reaction was carried out without stirring. Hydrogen was collected by drainage method, and the volume of water collected was the volume of NaBH 4 The volume of hydrogen produced by hydrolysis. Figure 4 The hydrogen production rate of the catalyst prepared in Example 1 of the present invention is shown in Figure 1. The hydrogen production rate is calculated based on the Co content in the added catalyst, and its unit is L·min -1 ·g Co -1 , the calculated hydrogen generation rate is 13.20 L·min -1 ·g Co -1 .

[0050] Figure 5 The Co 2p (a) and B1s (b) XPS spectra of the catalyst prepared in Example 1 of the present invention are analyzed. Figure 5 The fitting results of the XPS spectrum of Co 2p in (a) show that Co on the catalyst surface exists in two forms: metallic and oxidized. The proportion of metallic Co accounts for 73.5%, indicating that there are a large number of active Co sites on the catalyst surface. Figure 5 The XPS spectrum of B1s in (b) was fitted and analyzed, and it was found that the B element also existed in alloy form and oxidation state. The low binding energy of alloy B (187.7 eV) was shifted to the right by 0.6 eV compared with the binding energy of pure B (187.1 eV). This indicates that electron transfer occurred from alloy B to the vacant d orbital of metal Co, resulting in electron deficiency in B atoms and electron enrichment in Co atoms. This electron-enriched metal Co is considered to be NaBH 4 The catalytic active sites of hydrolysis play an important role in promoting the hydrolysis reaction. It is precisely because of the increase in electron density on the active Co site that the catalyst prepared in Example 1 exhibits excellent catalytic activity.

[0051] Figure 6 The hydrolysis hydrogen production diagram of the catalyst prepared in Example 1 of the present invention, the Arrhenius diagram corresponding to InK and 1 / T, from Figure 6 As can be seen in the left figure, when the reaction temperature increases from 303K to 318K, the hydrogen production rate increases from 13.20L·min -1 ·g Co -1Increased to 24.32L·min -1 ·g Co -1 As the temperature continues to rise, the hydrolysis reaction rate increases significantly, and the hydrolysis reaction follows zero-order kinetics. The activation energy Ea is calculated by the Arrhenius equation to be 30.4 kJ·mol -1 (like Figure 6 as shown in the figure on the right).

[0052] Figure 7 This is a stability test chart of the catalyst prepared in Example 1 of the present invention. After 5 repeated experiments, it still maintains 83.9% of the initial activity, indicating that the catalyst has good cyclic stability.

[0053] Example 2

[0054] This example prepares a SnO 2 The preparation method of the modified Co-B@C high-performance catalyst, the preparation process and steps are as follows:

[0055] (1) Add 2 g of 100-150 mesh dry coffee grounds to 4 mL of 3 mol / L ZnCl 2 The solution was stirred evenly, and after impregnation for 12 hours, it was poured into a crucible and kept in a muffle furnace at 300°C for 30 minutes. After cooling to room temperature, it was taken out and ground into 100-150 meshes, and then washed with deionized water until neutral, and dried at 120°C for 10 hours to obtain biomass carbon;

[0056] (2) Add 0.05 g of the biomass carbon obtained in step (1) to 0.0068 mol CoCl 2 6H 2 O and 0.0001 mol SnCl 4 ·5H 2 O mixed solution, and ultrasonically mixed at 30°C for 1 h to obtain a solution;

[0057] (3) The solution obtained in step (2) was placed in a water bath at 25°C and 30 mL of NaBH 4 Alkaline solution (NaBH 4 The alkaline solution was prepared by dissolving 1.5 g NaOH in 27 g deionized water to obtain an alkaline solution, and then adding 1.5 g NaBH 4 , stir and dissolve to obtain NaBH 4 The alkaline solution) was added to the solution obtained in step (2) at a drop rate of 2 mL / min. After the reaction was complete, the mixture was centrifuged and washed with deionized water and ethanol for three times respectively. The mixture was placed in a vacuum drying oven and dried in vacuum at 70° C. for 10 h to obtain a catalyst.

[0058] Example 3

[0059] This example prepares a SnO 2 The preparation method of the modified Co-B@C high-performance catalyst, the preparation process and steps are as follows:

[0060] (1) Add 2 g of 100-150 mesh dry coffee grounds to 4 mL of 3 mol / L ZnCl 2 The solution was stirred evenly, and after immersion for 12 hours, it was poured into a crucible and kept in a muffle furnace at 300°C for 30 minutes. After cooling to room temperature, it was taken out and ground to 100-150 mesh, and then washed with deionized water until neutral, and dried at 100°C for 11 hours to obtain biomass carbon;

[0061] (2) Add 0.05 g of the biomass carbon obtained in step (1) to 0.0068 mol CoCl 2 6H 2 O and 0.0001 mol SnCl 4 ·5H 2 O mixed solution, and ultrasonically mixed at 30°C for 1 h to obtain a solution;

[0062] (3) The solution obtained in step (2) was placed in a water bath at 25°C and 30 mL of NaBH 4 Alkaline solution (NaBH 4 The alkaline solution was prepared by dissolving 1.5 g NaOH in 27 g deionized water to obtain an alkaline solution, and then adding 1.5 g NaBH 4 , stir and dissolve to obtain NaBH 4 The alkaline solution) was added to the solution obtained in step (2) at a drop rate of 2 mL / min. After the reaction was complete, the mixture was centrifuged and washed with deionized water and ethanol for three times respectively. The mixture was placed in a vacuum drying oven and dried in vacuum at 65° C. for 11 h to obtain a catalyst.

[0063] Comparative Example 1

[0064] In order to explore the effect of Sn content in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were conducted. Different catalysts were prepared in the following comparative examples, as follows:

[0065]

[0066]

[0067] Comparative Example 2

[0068] In order to explore the influence of different parameters in the preparation process of the present invention on the performance of the product of the present invention, the following comparative experiments were carried out. Different catalysts were prepared in the following comparative examples, as follows:

[0069] Group D: This comparative example prepared a catalyst similar to that of Example 1, except that no biomass carbon was added in step (2).

[0070] Group E: This group of comparative examples prepared a catalyst similar to that of Example 1, except that in step (2), no tin chloride pentahydrate was added, and in step (1), the activator ZnCl 2 The concentration was changed to 1 mol / L, and the other parameters were the same as in Example 1.

[0071] Group F: This comparative example prepared a catalyst similar to that of Example 1, except that in step (2), no tin chloride pentahydrate was added, and in step (1), the activator ZnCl 2 The concentration was changed to 2 mol / L, and the other parameters were the same as in Example 1.

[0072] Group G: This comparative example prepared a catalyst similar to that of Example 1, except that in step (2), tin chloride pentahydrate was not added, and in step (1), the activator ZnCl 2 The concentration was changed to 4 mol / L, and the other parameters were the same as in Example 1.

[0073] Group H: This comparative example prepared a catalyst similar to that of Example 1, except that in step (2), no tin chloride pentahydrate was added, and in step (1), the activator ZnCl 2 The concentration was changed to 5 mol / L, and the other parameters were the same as in Example 1.

[0074] Group I: This group of comparative examples prepares a catalyst similar to that of Example 1, except that in step (2), tin chloride pentahydrate is not added, and the calcination temperature for preparing biomass carbon in step (1) is changed to 400°C. The remaining parameters are the same as those of Example 1.

[0075] Group J: This group of comparative examples prepared a catalyst similar to that of Example 1, except that in step (2), tin chloride pentahydrate was not added, and the calcination temperature for preparing biomass carbon in step (1) was changed to 500°C. The remaining parameters were the same as those of Example 1.

[0076] Group K: This group of comparative examples prepared a catalyst similar to that of Example 1, except that in step (2), tin chloride pentahydrate was not added, and the calcination temperature for preparing biomass carbon in step (1) was changed to 600°C. The remaining parameters were the same as those of Example 1.

[0077] Group L: This comparative example prepared a catalyst similar to that of Example 1, except that in step (2), no tin chloride pentahydrate and biomass carbon were added.

[0078] The above AI group comparison ratio was subjected to morphological characterization and hydrogen production rate test, and the test results are as follows:

[0079]

[0080] It can be seen from the table that the hydrogen production rates of the catalysts prepared in the DL group comparative examples are lower than those of the catalysts prepared in Example 1 of the present invention. This shows that the catalysts prepared by the preparation method provided by the present invention have better performance.

[0081] Comparative Example 3

[0082] In order to explore the effects of different carbon sources on the performance of the prepared catalyst, this comparative example conducted the following comparative tests, as follows:

[0083] 6 mL of graphene oxide (2 mg / mL) was added to the beaker, and 1 mL of CoSO 4 7H 2 O (0.1 M), 1 mL sodium citrate (0.3 M), and 0.1 mL SnCl 4 (0.3 M) was also added to the beaker and ultrasonicated for 20 min to obtain a mixed solution. At the same time, 50 mL of 5 wt.% NaOH and 5 wt.% NaBH 4 The solution was placed in a 30°C water bath; then the mixed solution was quickly injected with NaBH 4 The solution immediately turned dark black and bubbles were generated. After the reaction was completed, the solution was centrifuged and washed with water and alcohol respectively. The prepared Co-Sn-B / GO catalyst was spherical particles with a hydrogen production rate of 11.27 L·min -1 ·g Co -1 , the activation energy is 39.6 kJ·mol -1 .

[0084] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a SnO2-modified Co-B@C high-performance catalyst, characterized in that: Follow the steps below in order: (1) Adding dry coffee grounds to a ZnCl2 solution and stirring evenly, pouring into a crucible after soaking for 12 hours, and keeping in a muffle furnace at 300°C for 30 minutes, cooling to room temperature, taking out and grinding, then washing with deionized water until neutral, and drying at 100-120°C for 10-12 hours to obtain biomass carbon; (2) adding the biomass carbon obtained in step (1) to a mixed solution of CoCl2·6H2O and SnCl4·5H2O, and performing ultrasonication until the mixture is uniformly mixed to obtain a solution; (3) The solution obtained in step (2) is placed in a water bath at a temperature of 25° C. Under the action of magnetic stirring, an alkaline solution of NaBH4 is added to the solution obtained in step (2). After the reaction is complete, the solution is centrifuged and washed with deionized water and ethanol three times respectively, and then placed in a vacuum drying oven to dry to obtain a catalyst.

2. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (1), the particle size of the dried coffee grounds is 100-150 mesh.

3. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (1), the mass ratio of the dry coffee grounds to the ZnCl2 solution is 1:2.

8.

4. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (1), the concentration of the ZnCl2 solution is 3 mol / L.

5. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (2), the molar ratio of CoCl2·6H2O to SnCl4·5H2O is 68:

1.

6. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (2), the mass ratio of the biomass carbon to CoCl2·6H2O is 1:32.

4.

7. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (3), the dropping rate of the alkaline solution of NaBH4 is 2 mL / min.

8. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (3), the preparation process of the NaBH4 alkaline solution is: 1.5g NaOH is completely dissolved in 27g deionized water to obtain an alkaline solution, and then 1.5g NaBH4 is added to the solution, and stirred to dissolve to obtain an alkaline solution of NaBH4.

9. The method for preparing a SnO2-modified Co-B@C high-performance catalyst according to claim 1, characterized in that: In step (3), the drying temperature is 60-70°C and the drying time is 10-12h.